Intersectionality Pedagogy in the Classroom: Experiences of Counselor Educators - Jenae D. Thompson; Corinne W Bridges (Teaching and Supervision in Counseling, 2019)
The role of intersectionality in counselor education and supervision has not been formally addressed by researchers in the preparation of counselors in training. Traditional ways of teaching multicultural and diversity issues in counseling include compartmentalized discussions about social identities, but do not incorporate intersectionality despite its significance in describing how individuals move through the world. The method of inquiry used to collect and analyze data was heuristic in nature due to the focus on contextual experiences of the participants as well as the researcher. The results showed how seven CES faculty members’ personal and professional experiences influenced their incorporation of intersectionality in their multicultural pedagogy. The extent to which intersectionality plays a role in understanding multicultural counseling education and experiences of faculty members is explored in this article.
Keywords: Multicultural pedagogy; intersectionality; counselor educators and supervisors; counselors-in-training; heuristic inquiry